Growth of Human Dermal Fibroblasts on Polyvinyl Alcohol-Silk Fibroin Nanofiber Scaffold - Regina Giovanni; Untung Ari Wibowo; Hermawan Judawisastra; Anggraini Barlian (Institute for Research and Community Services (LPPM) ITB, 2019)
Skin tissue engineering is a developing technology to heal severe wounds. Combining polyvinyl alcohol (PVA) and silk fibroin (SF) nanofibers is a promising method of developing a skin scaffold because the resulting structure mimics collagen fibers. The aim of this research was to study the growth of human dermal fibroblasts (HDF) on a polyvinyl alcohol-silk fibroin (PVA-SF) nanofiber scaffold that was produced by electrospinning. Morphological characterization and chemical analysis of the scaffold were performed by scanning electron microscopy (SEM), Fourier transform infrared spectrophotometry (FTIR), and contact angle measurement. The biocompatibility of the scaffold was tested by MTT cytotoxicity assay, SEM analysis, adherence ratio calculation, and analysis of the HDF growth curve for 9 days. The FTIR results confirmed the presence of SF and PVA. The average fiber diameter and pore size of the PVA scaffold were greater than those of the PVA-SF scaffold. Both scaffolds had hydrophilic properties and were not cytotoxic. Thus, HDF can attach and grow on both types of scaffold better than HDF seeded on a polystyrene plate. In conclusion, the addition of SF to the PVA nanofibers caused bead formation, which affected the substrate topography, decreased hydrophilicity and also decreased the fiber diameter and pore size in the nanofiber scaffold compared to the PVA nanofiber scaffold without SF addition. SF addition increases cell attachment to the nanofiber scaffold and has potential to facilitate HDF cell growth.